2020
DOI: 10.1136/bmjopen-2020-039035
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of the Pediatric Urology Recovery After Surgery Endeavor (PURSUE) multicentre pilot and exploratory study

Abstract: IntroductionLower urinary tract reconstruction in paediatric urology represents a physiologically stressful event that is associated with high complication rates, including readmissions and emergency room visits. Enhanced recovery after surgery (ERAS) protocol is a set of multidisciplinary, perioperative strategies designed to expedite surgical recovery without adversely impacting readmission or reoperation rates. Early paediatric urology data demonstrated ERAS reduced complications in this population.Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Trends toward improved pain scores, reduced number of rescue doses, and PONV are suggestive of key areas for study. This information could be impactful for the design, implementation, and success of enhanced recovery after surgery (ERAS) pathways ( 15 , 16 , 40 ). The impact of prolonged duration of anesthesia on the progression to persistent pain is another key question for exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trends toward improved pain scores, reduced number of rescue doses, and PONV are suggestive of key areas for study. This information could be impactful for the design, implementation, and success of enhanced recovery after surgery (ERAS) pathways ( 15 , 16 , 40 ). The impact of prolonged duration of anesthesia on the progression to persistent pain is another key question for exploration.…”
Section: Discussionmentioning
confidence: 99%
“…While both techniques can be safely and successfully applied, there is limited data specifically related to the impact on the quality of postoperative analgesia, recovery, and efficiency of care when TAP block or caudal block are part of multimodal analgesia for lower abdominal surgeries in children. Such information is vitally important in an era increasingly focused on cost-effective patient-centered care that can resonate beyond the operating suite, such as enhanced recovery efforts ( 15 , 16 ). This meta-analysis can help address this gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Adult and existing pediatric ERAS protocols were reviewed. The Pediatric Urology Recovery After Surgery Endeavor (PURSUE) trial formed the basis of the protocol, given its success ( 13 ) and similarities in surgical complexity to the pediatric oncology patient population ( 14 ). The study team determined protocol inclusion criteria based on literature review, observed issues in pediatric patients undergoing solid tumor resections, and group consensus.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Meanwhile, evidence in pediatrics suggests that a clear liquid carbohydrate drink may promote a more stable perioperative metabolic state, particularly for longer operations (29). Based on existing data, a group of pediatric urologists and anesthesiologists have incorporated a preoperative clear liquid complex carbohydrate load into their revised ERAS protocols for lower urinary tract reconstructions (30).…”
Section: Preoperative Fasting and Carbohydrate Loadingmentioning
confidence: 99%
“…This particular example illustrates the consideration in outcomes among different patient populations when evaluating whether intended effects of ERAS elements are equally distributed. Overall, foregoing this step has been a welcome addition to ERAS protocols for many institutions due to improved perioperative experiences for patients and reductions in costs associated with decreased LOS (9,30,31).…”
Section: Elimination Of Mechanical Bowel Preparationmentioning
confidence: 99%